The value of 18F⁃FDG PET in the diagnosis and differential diagnosis of Parkinson's disease and multiple system atrophy with parkinsonism⁃predominant - DU Xiao‐xiao; DONG Wan‐hui; LI Yi; SUN Zhi‐hui; FAN Kang‐li; ZHANG Ying (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To investigate the value of 18F⁃FDG PET in the diagnosis and differential diagnosis of Parkinson's disease (PD) and multiple system atrophy with parkinsonism⁃predominant (MSA⁃P). Methods Total 96 patients with PD and 52 patients with MSA ⁃ P from The First Hospital of Jilin University from May 2019 to December 2022 were included, and 18F⁃FDG PET data were collected from all patients and 18F⁃FDG PET data was analyzed using CortexID Suite software. The diagnostic and differential diagnostic efficacy of PD and MSA⁃P of 18F⁃FDG PET was evaluated using the receiver operating characteristic (ROC) curve and area under the curve (AUC). The Z ⁃ scores of 26 brain regions were obtained, and the brain glucose metabolism patterns of patients with PD and MSA⁃P were finally obtained by comparing with the normal control database. The consistency between 18F⁃FDG PET and "gold standard" diagnosis was evaluated using the Kappa test. Results 1) Metabolic pattern: compared with the normal control database, the PD group showed significantly hypermetabolism in pons (t = 2.851, P = 0.005), cerebellum (t = 2.295, P = 0.024) and mesial temporal (t = 5.850, P = 0.000), and significantly hypometabolism in lateral occipital (t = ⁃ 7.116, P = 0.000), superior parietal (t = ⁃ 13.466, P = 0.000), inferior parietal (t = ⁃ 21.838, P = 0.000), precuneus (t = ⁃ 7.121, P = 0.000), sensorimotor (t = ⁃ 6.931, P = 0.000) and lateral prefrontal (t = ⁃ 6.778, P = 0.000); while the MSA⁃P group showed significant hypometabolism in pons (t = ⁃ 8.364, P = 0.000), cerebellum (t = ⁃ 9.900, P = 0.000), superior parietal (t = ⁃ 4.830, P = 0.000) and inferior parietal (t = ⁃ 11.287, P = 0.000), and hypermetabolism in the primary visual (t = 5.579, P = 0.000). 2) Diagnosis and differential diagnosis: compared with the MSA⁃P group, the PD group had lower Z⁃score in sensorimotor (t = ⁃ 0.646, P = 0.008), precuneus (t = ⁃ 4.516, P = 0.000), superior parietal (t = ⁃ 4.611, P = 0.000), inferior parietal (t = ⁃ 5.903, P = 0.000), lateral occipital (t = ⁃ 5.088, P = 0.000) and primary visual (t = ⁃ 3.218, P = 0.002), while the Z⁃scores in mesial temporal (t = 3.718, P = 0.002), cerebellum (t = 9.880, P = 0.000) and pons (t = 9.520, P = 0.000) were higher. The ROC curve was drew for the differential diagnostic efficacy of 18F⁃FDG PET through the six brain regions with statistical difference and P = 0.000 between the 2 groups, the result showed that the AUC of cerebellum (Z = 3.595, P = 0.000; Z = 2.942, P = 0.003; Z = 2.942, P = 0.003; Z = 3.519, P = 0.000), pons (Z = 3.363, P = 0.001; Z = 3.237, P = 0.000; Z = 2.376, P = 0.018; Z = 3.012, P = 0.003) and the combination of the six brain regions (Z = 4.354, P = 0.000; Z = 4.242, P = 0.000; Z = 3.711, P = 0.000; Z = 4.233, P = 0.000) were bigger than the AUC of precuneus, superior parietal, inferior parietal and lateral occipital; the AUC of the combination of the six brain regions was bigger than pons (Z = 1.986, P = 0.047). Kappa test indicated that the diagnosis of the 18F⁃FDG PET had good agreement with the diagnosis of the "gold standard" in the two diseases (κ = 0.678, P = 0.000, for all). Conclusions The characteristic brain glucose metabolism patterns of PD and MSA⁃P can be obtained by 18F⁃FDG PET. 18F⁃FDG PET has good diagnostic and differential diagnostic efficacy for PD and MSA⁃P.